Ultrafast Charge Rearrangement and Nuclear Dynamics upon Inner-Shell Multiple Ionization of Small Polyatomic Molecules - Erk, B.; Rolles, D.; Foucar, L.; Rudek, B.; Epp, S. W.; Cryle, M.; Bostedt, C.; Schorb, S.; Bozek, J.; Rouzee, A.; Hundertmark, A.; Marchenko, T.; et al. (My University, 2013)
Ionization and fragmentation of methylselenol (CH3SeH) molecules by intense (>1017 W/cm2) 5 fs x-ray pulses (ℏω=2 keV) are studied by coincident ion momentum spectroscopy. We contrast the measured charge state distribution with data on atomic Kr, determine kinetic energies of resulting ionic fragments, and compare them to the outcome of a Coulomb explosion model. We find signatures of ultrafast charge redistribution from the inner-shell ionized Se atom to its molecular partners, and observe significant displacement of the atomic constituents in the course of multiple ionization.